KOMUNIKASI TRANSENDENTAL APLIKASINYA SEPERTI APA? - Gunadi, YS (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
Unusualy, the   elements  of  communication  activities  there   are com-municator,  message, and communicant. But, why is  commu- nication   religion  as prayer  believed to  the God?  God  is  not  material like the  man,  not  can  see by our eyes. If every  one  praying to the God,  where  is God,  God not clear  in front our faces.  Prayer activities belong  communication models  or not?Nearly intelectualities of communication  make  the  definition, pra-ying   activitities, althought  not clear  who  was the  communicant,but  is  communication. The mane  of  communications activities ia trancendental  communication. The hung of transcendental com- munication to tell to you with the story illustrationat unders.